Estimated extent of purchasing of antibiotics without a prescription from community pharmacies in a rural province in South Africa and the implications - Maluleke, Tiyani Milta; Maluleke, Morgan Tiyiselani; Jelic, Ana Golić; Campbell, Stephen M.; Marković-Peković, Vanda; Schellack, Natalie; Chigome, Audrey; Cook, Aislinn; Godman, Brian; Meyer, Johanna C. (Frontiers in Tropical Diseases, 2025)
BackgroundAntimicrobial resistance is a considerable global health threat especially among low- and middle-income countries, exacerbated by considerable inappropriate dispensing of antibiotics. There have though been concerns with variable levels of dispensing of antibiotics without a prescription in South Africa. Consequently, a need to comprehensively estimate current levels of dispensing of antibiotics without a prescription, which was the aim of this study.MethodsAdminister a previously piloted questionnaire to all currently operating community pharmacies in a rural province, where dispensing of antibiotics without a prescription is likely to be greatest. The questionnaire included data on the estimated prevalence of antibiotics dispensed, their class and indication, and whether dispensed without a prescription. Community pharmacies were categorized into three: Independent, Chain and Franchise.Results128/169 (75.7%) operational pharmacies participated, with independent pharmacies representing the majority (60.9%). There was a 78.3% response rate from 400 distributed questionnaires, including 106 pharmacists (33.9%) and 207 pharmacist assistants (66.1%) from 128 pharmacies. Antibiotics accounted for 47.9% (95% CI: 47.2%-48.6%) of all medicines dispensed. Penicillins were the most prevalent antibiotic dispensed (41.1%). Almost half (47.2%) of the antibiotics dispensed included macrolides, fluoroquinolones and cephalosporins, which are typically antibiotics from the Watch group. Sexually transmitted infections (33.5%) and upper respiratory tract infections (25.8%) were the most frequent indications for antibiotic dispensing. Overall, 69.3% of 128 participating pharmacies in this rural province in South Africa admitted to dispensing antibiotics without a prescription in the past 14 days, principally among independent pharmacies (98.7%). However, estimates suggest only 8.6% of the total volume of antibiotics being dispensed were dispensed without a prescription among the 88 community pharmacies admitting to this practice in the past 3 days. Encouragingly, 98.1% of community pharmacists and 97.6% of pharmacist assistants indicated they always or mostly offered symptomatic relief before dispensing antibiotics without a prescription to patients with self-limiting conditions.ConclusionThere were considerable concerns regarding the prescribing and dispensing of antibiotics in this rural province including Watch antibiotics. This included the number of community pharmacies, especially independent pharmacies, where patients could purchase antibiotics without a prescription. Multiple strategies involving all key stakeholder groups are need to improve future antibiotic use across South Africa and reduce AMR.